TERAPI MURROTAL QUR’AN PADA PENDERITA HIPERTENSI DENGAN KELUHAN NYERI LEHER - Mujahidin; Ayu Lestari (LPPM STIKes Mitra Adiguna, 2024)
Hypertension is a condition where there is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. Hypertension that occurs causes several complaints and one of them is complaints of pain in the neck area. Several therapies are used in the management of neck pain in hypertensive sufferers, either using pharmacological or non-pharmacological therapy. Murrotal Qur'an from the results of the study appears to have been widely used as an alternative non-pharmacological therapy in various cases related to pain. The aim of this research is to find out the effect of the Murrotal Qur'an on neck pain in hypertension sufferers. This research is a pre-experimental one group pre test-post test design research. The sample consisted of 34 people with hypertension who were selected using purposive sampling technique. The research was carried out in the work area of ??the Lumpatan Community Health Center, Musi Banyuasin Regency, South Sumatra Province. The results of statistical tests using the Paired T test obtained a p value of 0.000. Based on these results, it was concluded that there was a significant influence of Murrotal Qur'an on neck pain in hypertension sufferers Keywords: Murrotal Qur'an, Neck Pain, Hypertension